Novel targets to develop new antibacterial agents and novel alternatives to antibacterial agents. (March 2019) - Belete, Tafere Mulaw
Abstract: Antibacterial agents have saved many lives and helped the growth of modern medicine over the past half century. The emergence of drug resistance, jeopardizing the effectiveness of these life-saving treatments. This clearly highlights the urgent need for new and improved antibacterial drugs with a novel target and new molecular structure agent to obviate cross-resistance. This paper reviewed the possible new ways to discover novel antibacterial agents. The most widely studied new bacterial targets for novel drug development are quorum sensor biosynthesis, bacterial virulence factor, bacteria cell division machinery, Bacterial cell wall synthesis, PDF inhibitor, isoprenoid biosynthesis, shikimate synthesis pathway, biofilm synthesis and fatty acid biosynthesis. These new discovery routes have given rise to agents that are in preclinical trials. This review also discusses the alternatives approaches that act bacteria or any approaches that target the host. The most advanced approaches that are on clinical development are phages and other approaches that are on preclinical development are antimicrobial peptides. These alternatives ways may use as adjunctive therapies, which suggest that conventional antibacterial agents are still essential.